PREDICTING LEARNING FROM ASYNCHRONOUS ONLINE DISCUSSIONS - Dezhi Wu; Starr Roxanne Hiltz (Online Learning, 2019)
Online discussions play an important role in student learning. Currently, asynchronous learning courses and some primarily face-to-face courses at New Jersey Institute of Technology require asynchronous online discussions. Does this requirement improve the students’ perceived learning? An exploratory study designed to investigate this issue was conducted in Spring 2002. The questionnaire drew responses to a post-course questionnaire from 116 students in two undergraduate courses and one graduate course. A set of items designed to measure perceived learning from online discussions formed a reliable, unidimensional index for this construct. The results indicate that online discussions do improve students’ perceived learning. Variations among instructors or courses are associated with differences in perceptions of student motivation, enjoyment, and learning from online discussion. Open-ended questions identified some student concerns about online discussions. The concluding section of this paper presents some implications for improving online discussions and for future research plans.